2011
DOI: 10.1007/s00595-011-0049-9
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory response syndrome as a predictor of anastomotic leakage after esophagectomy

Abstract: The SIRS scoring system is valuable for evaluating the severity of systemic inflammatory response caused by anastomosis leakage, and may serve as an indicator for prompt management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 21 publications
3
30
1
Order By: Relevance
“…Other studies have confirmed this suggestion [1, 16, 23, 28, 53, 54]. The results of the present meta-analysis confirm these results demonstrating that average values of CRP differ between patients with and without infectious complications.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Other studies have confirmed this suggestion [1, 16, 23, 28, 53, 54]. The results of the present meta-analysis confirm these results demonstrating that average values of CRP differ between patients with and without infectious complications.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, this discrepancy between types of abdominal surgery can only exist in the first 2 days due to the short half-life of CRP (19 h). The trend where CRP values tend to normalize in patients without infectious complications around POD 3 has been demonstrated for various types of surgery [1, 16, 23, 28, 53, 54]. The major advantage of combining different types of abdominal surgery is that a much larger sample size was reached resulting in more precise estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Esophagectomy, in and of itself, appears to have a heighted influence on the postoperative inflammatory cascade compared to other cancer operations,(2022) independent of infectious or inflammatory complications. (23) In addition, several studies have shown that baseline upregulation of tumor inflammation-associated genes, inflammatory markers, and inflammation-based preoperative prognostic scores are predictive of worse prognosis. (2431) This increase in cytokines and inflammatory molecules is present as much as 2 years prior to diagnosis.…”
Section: Commentmentioning
confidence: 99%
“…All leaks with less than 20 mm were solved endoscopically. Technical and clinical success was higher when time between surgery and SEMS placement was lower, even though without statistical significance (respectively, 10 days [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] vs. 48 days , p = 0.228 and 12 days [8][9][10][11][12][13][14][15][16][17][18][19][20][21] vs. 20 days , p = 0.374) (Fig. 1).…”
Section: Sems Placement and Adverse Eventsmentioning
confidence: 99%
“…Clinical manifestations vary depending on the location of the leak and time elapsing from the perforation or rupture. Fever, systemic inflammatory response syndrome, and abnormal C-reactive protein, white blood cell count, and albumin are indicators of postoperative esophageal leak (8,9).…”
Section: Introductionmentioning
confidence: 99%